Changes in thyroid function levels in female patients with first-episode bipolar disorder - Song, Xiuhua; Feng, Yufang; Yi, Lei; Zhong, Baoliang; Li, Yi (Frontiers in Psychiatry, 2023)
Objectives The identification of molecular biomarkers for bipolar disorder is anticipated to greatly improve the diagnosis and treatment of this disease. The objective of this case–control study is to determine whether the blood thyroid hormone levels in bipolar disorder patients are associated with different types of first onset. Methods From August 1, 2020 to July 31, 2021 a total of 120 female patients diagnosed with bipolar disorder and hospitalized at Qingdao Mental Health Center were recruited as the case group, including 60 patients with depression as their first onset (depression first-episode group, DF) and 60 with mania/hypomania as their first onset (mania/hypomania first-episode group, M/HF). A group of 60 healthy adult females matching general demographic data, such as race and age, were selected as the control group. Blood samples were taken from both groups to measure serum triiodothyronine (T3), thyroxine (T4), free triiodothyronine (FT3), free thyroxine (FT4), and thyroid stimulating hormone (TSH) concentrations. Results The duration of current onset in the M/HF group was significantly less than that in the DF group (23.1 ± 20.2 vs. 125.2 ± 41.0 days). About 27% of patients in the M/HF group had thyroid abnormalities, in contrast to 60% in the DF group. The blood T3 and T4 levels in both the M/HF group and the DF group, as well as the TF3 levels in the DF group, were significantly lower as compared to control. The M/HF group had significantly higher T3 and FT3 levels than the DF group. The blood T3 levels were inversely correlated with the Young’s Mania Scale score and the Hamilton Depression Scale score in both the M/HF and DF groups. Conclusion Thyroid dysfunction resulting in reduced levels of blood thyroid levels may be involved in the disease progression of bipolar disorder, and correlated with the clinical symptoms in patients with depression or mania as the first episode.